2018
DOI: 10.1002/gj.3326
|View full text |Cite
|
Sign up to set email alerts
|

Diagenetic characteristics and reservoir quality in tight gas sandstones: A case study of the Shanxi Formation in the north‐eastern Ordos Basin, China

Abstract: Reservoir quality is critical in tight gas exploration. A systematic study of the petrological, petrophysical, and diagenetic characteristics of the Shanxi Formation sandstones in the north‐eastern Ordos Basin (China) was undertaken to characterize the pore system of these tight sandstones and recognize the distribution of reservoirs favourable for hydrocarbon accumulation. The results suggest that the Shanxi Formation sandstone has low compositional and moderate textural maturity, with its porosity ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…According to data from the National Institute Standards and Technology (NIST), the corresponding gas densities of the initial structure of three soaking systems under reservoir conditions are 0.30 g/cm 3 (N 2 soaking system), 0.82 g/cm 3 (CO 2 soaking system), and 0.415 g/cm 3 (hybrid N 2 –CO 2 soaking system). Tight and ultratight shale oil reservoir matrices are characterized by heterogeneous rock compositions comprising both organic and inorganic matter. , Among the various inorganic minerals, quartz is reported to be one of the most common inorganic minerals in which numerous nanopores are well-developed. , In addition, quartz is highly brittle, which means that shale is prone to inherent and induced cracks under the action of external forces and is ultimately conducive to gas intrusion into the matrix and shale oil recovery. , In this work, the general soaking law of gas HnP in the shale reservoir is reflected based on the characteristics and conditions of shale oil reservoirs of the Lucaogou Formation in the Jimsar Sag, Xinjiang oilfield, China . Furthermore, previous mineral component analysis of shale core samples from the Jimsar reservoir showed that the mineral composition of the Lucaogou Formation shale matrix is complex and diverse, but quartz has the highest relative content and plays an important role. , Thus, a single mineral, quartz, is used in this work to represent the shale reservoir matrix.…”
Section: Models and Methodologymentioning
confidence: 95%
See 1 more Smart Citation
“…According to data from the National Institute Standards and Technology (NIST), the corresponding gas densities of the initial structure of three soaking systems under reservoir conditions are 0.30 g/cm 3 (N 2 soaking system), 0.82 g/cm 3 (CO 2 soaking system), and 0.415 g/cm 3 (hybrid N 2 –CO 2 soaking system). Tight and ultratight shale oil reservoir matrices are characterized by heterogeneous rock compositions comprising both organic and inorganic matter. , Among the various inorganic minerals, quartz is reported to be one of the most common inorganic minerals in which numerous nanopores are well-developed. , In addition, quartz is highly brittle, which means that shale is prone to inherent and induced cracks under the action of external forces and is ultimately conducive to gas intrusion into the matrix and shale oil recovery. , In this work, the general soaking law of gas HnP in the shale reservoir is reflected based on the characteristics and conditions of shale oil reservoirs of the Lucaogou Formation in the Jimsar Sag, Xinjiang oilfield, China . Furthermore, previous mineral component analysis of shale core samples from the Jimsar reservoir showed that the mineral composition of the Lucaogou Formation shale matrix is complex and diverse, but quartz has the highest relative content and plays an important role. , Thus, a single mineral, quartz, is used in this work to represent the shale reservoir matrix.…”
Section: Models and Methodologymentioning
confidence: 95%
“…45,46 Among the various inorganic minerals, quartz is reported to be one of the most common inorganic minerals in which numerous nanopores are well-developed. 47,48 In addition, quartz is highly brittle, which means that shale is prone to inherent and induced cracks under the action of external forces and is ultimately conducive to gas intrusion into the matrix and shale oil recovery. 49,50 In this work, the general soaking law of gas HnP in the shale reservoir is reflected based on the characteristics and conditions of shale oil reservoirs of the Lucaogou Formation in the Jimsar Sag, Xinjiang oilfield, China.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The burial depth was 1500-2200 m, and the paleotemperature ranged from 70 • C to 90 • C (Figure 8). The Shanxi Formation is a coal measure stratum, H + is produced under oxidation conditions [58], promoting the occurrence of dissolution [52,56,59]. By observing the homogenization temperature of inclusions in quartz cement, a large number of inclusions were formed in this period and oil and gas began to appear (Figure 9).…”
Section: Eodiagenesismentioning
confidence: 99%
“…Figure 9. Diagenetic evolution sequence and pore evolution of sandstone of the Shanxi Formation in the HangJinqi area (Curve data of burial history from Xinhe Shao, 2018[58]. Gas filling data from Zhou Jinsong, 2020[59]).…”
mentioning
confidence: 99%